Analysis of the Regularity and Mechanism of Fault Activation Caused by Deep Continuous Mining of Shizishan Copper Mine, China - Yanhui Guo; Luo Luo; Hanhua Xu; Chun Zhu (Advances in Materials Science and Engineering)
In order to study the law and mechanism of fault activation induced by deep continuous mining, this paper takes the fault activation caused by underground mining of Shizishan Copper Mine as the research object. On the basis of field investigation and theoretical analysis of fault activation, the law and mechanism of fault group activation induced by deep continuous mining in the Shizishan mining area are analyzed in detail based on the three-dimensional discrete element method software 3DEC. The results show that the fault effect of rock movement in the footwall of the main orebody in the mine area is obvious. The en echelon steep dipping fault group in the footwall of the goaf will move each fault block in the direction of the goaf and slip along the fault plane when the balance between mining and gravity is disrupted. The fault activation has a domino effect in time and space, and the mechanism of this effect is revealed. The research results have great significance for the deep mining area development, mining alignment arrangement, and disaster prevention and control caused by fault activation.